Therapeutic Effects of Tryptanthrin and Tryptanthrin-6-Oxime in Models of Rheumatoid Arthritis - Liliya N. Kirpotina; Igor A. Schepetkin; Deepa Hammaker; Amanda Kuhs; Andrei I. Khlebnikov; Andrei I. Khlebnikov; Mark T. Quinn (Frontiers Media S.A., 2020)
Rheumatoid arthritis (RA) is a chronic autoimmune disease involving joint and bone damage that is mediated in part by proteases and cytokines produced by synovial macrophages and fibroblast-like synoviocytes (FLS). Although current biological therapeutic strategies for RA have been effective in many cases, new classes of therapeutics are needed. We investigated anti-inflammatory properties of the natural alkaloid tryptanthrin (TRYP) and its synthetic derivative tryptanthrin-6-oxime (TRYP-Ox). Both TRYP and TRYP-Ox inhibited matrix metalloproteinase (MMP)-3 gene expression in interleukin (IL)-1β-stimulated primary human FLS, as well as IL-1β-induced secretion of MMP-1/3 by FLS and synovial SW982 cells and IL-6 by FLS, SW982 cells, human umbilical vein endothelial cells (HUVECs), and monocytic THP-1 cells, although TRYP-Ox was generally more effective and had no cytotoxicity in vitro. Evaluation of the therapeutic potential of TRYP and TRYP-Ox in vivo in murine arthritis models showed that both compounds significantly attenuated the development of collagen-induced arthritis (CIA) and collagen-antibody-induced arthritis (CAIA), with comparable efficacy. Collagen II (CII)-specific antibody levels were similarly reduced in TRYP- and TRYP-Ox-treated CIA mice. TRYP and TRYP-Ox also suppressed proinflammatory cytokine production by lymph node cells from CIA mice, with TRYP-Ox being more effective in inhibiting IL-17A, granulocyte-macrophage colony-stimulating factor (GM-CSF), and receptor activator of nuclear factor-κB ligand (RANKL). Thus, even though TRYP-Ox generally had a better in vitro profile, possibly due to its ability to inhibit c-Jun N-terminal kinase (JNK), both TRYP and TRYP-Ox were equally effective in inhibiting the clinical symptoms and damage associated with RA. Overall, TRYP and/or TRYP-Ox may represent potential new directions for the pursuit of novel treatments for RA.